The Reflection of Cultural Values in PanggilanTradisi Short Stories by Denny Agung: A Literary Analysis: Penelitian - Putra Darma, Virga; Alting, Hosam; Rachmawati, Valia (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This qualitative study investigates how cultural values are reflected in the short story Panggilan Tradisi, and how readers interpret these values through their own cultural lenses. Using in-depth interviews with eleven university students, the research explores participants’ perceptions of cultural indicators embedded in the story, such as traditional rituals, linguistic politeness, social harmony, and symbolic elements like wayang, gamelan, and blangkon. Findings show that the short story effectively conveys complex cultural values through concise narrative structure, character development, and setting. Readers’ interpretations were deeply influenced by their cultural backgrounds, prior experiences, and emotional proximity to the values represented. The results suggest that short stories can serve as powerful tools for fostering intercultural understanding and identity reflection. Additionally, the study underscores the significance of cultural analysis in literature as a means to promote empathy, tolerance, and a more critical awareness of societal values in a multicultural context.